Analisis Implementasi Shariah Compliance Pembiayaan Qardhul Hasan pada Lembaga Mikro Keuangan Syariah di Jawa Barat - Nashrul Fauzi; Robbani Robbani; Ivo Dinasta Yanuar (CIEBER: Contemporary Islamic Economic and Business Review, 2025)
One of the phenomena that occurs in the application of qardhul hasan at KSPPS BMT Al Falah is still not running optimally, because there are several members receiving qardhul hasan financing who are constrained. So an investigation will be carried out first on members who are unable to pay by closing their debts through zakat and infaq funds. The purpose of this study is based on the formulation of the existing problem, namely, to find out how the implementation of qardhul hasan financing is. What are the uses that loan customers will get from Qardhul Hasan financing? As well as the challenges and solutions in the implementation of Qardhul Hasan financing at BMT Al Falah. In this study, the author uses a descriptive qualitative method. In this study, the author uses primary data. The number of samples used in this study was 3 respondents. Data collection techniques used observation and interview methods. Data analysis techniques used data reduction, data presentation, and drawing conclusions implementation of Qardhul Hasan financing at BMT Al Falah has been carried out in accordance with the principles stipulated in the DSN-MUI Fatwa No.19/DSN-MUI/IV/2001. This is supported by the important role of the Sharia Supervisory Board (DPS) through monthly reports and regular discussions to ensure compliance with Sharia Principles. The training and outreach carried out before the distribution of Qardhul Hasan also helps educate employees and customers about sharia principles, thereby minimizing the potential for violations. The implementation of Qardhul Hasan financing at BMT Al Falah is supported by several supporting factors, such as intensive assistance to members, strong commitment from the internal BMT, and compliance with DSN-MUI regulations.